2002
DOI: 10.1197/aemj.9.7.661
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Emergency Department Patients with Sepsis

Abstract: Objective: To test the hypothesis that heart rate variability (HRV) can provide an early indication of illness severity among patients presenting to the emergency department (ED) with sepsis. Methods: The authors enrolled a convenience sample of 15 ED patients meeting the American College of Chest Physicians/Society of Critical Care Medicine criteria for sepsis. Each patient had continuous Holter monitoring performed in the ED. Acute Physiology and Chronic Health II (APACHE II) and Sequential Organ Failure (SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 36 publications
(37 reference statements)
1
30
1
1
Order By: Relevance
“…In contrast to our earlier study demonstrating the utility of HRV in predicting morbidity and mortality,21 our findings do not support the use of the LF/HF ratio by itself as an initial triage tool to identify moderately ill ED patients with sepsis at increased risk for short-term deterioration. Although there was a statistically significant relationship between the LF/HF ratio and short-term deterioration, this measure of HRV, obtained at presentation, by itself failed to consistently identify those patients who subsequently met one or more of the study endpoints, as reflected by the finding that 66% (21/32) of the patients who deteriorated had an LF/HF ratio >1 and would therefore have been incorrectly categorised using this criterion.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our earlier study demonstrating the utility of HRV in predicting morbidity and mortality,21 our findings do not support the use of the LF/HF ratio by itself as an initial triage tool to identify moderately ill ED patients with sepsis at increased risk for short-term deterioration. Although there was a statistically significant relationship between the LF/HF ratio and short-term deterioration, this measure of HRV, obtained at presentation, by itself failed to consistently identify those patients who subsequently met one or more of the study endpoints, as reflected by the finding that 66% (21/32) of the patients who deteriorated had an LF/HF ratio >1 and would therefore have been incorrectly categorised using this criterion.…”
Section: Discussioncontrasting
confidence: 99%
“…The ratio of low-frequency power to high-frequency power (LF/HF ratio) has been used as a summary measure of autonomic function 20. In 2001, we performed a pilot study of 14 ED patients with sepsis and found that all patients admitted to the ICU who required invasive critical care support or died had LF/HF ratios less than 1 21. Subsequent investigators have found similar associations between altered HRV and illness severity,22 development of multiple organ dysfunction syndrome,23 success or failure of early resuscitation,24 development of septic shock25 and in-hospital mortality 26…”
Section: Introductionmentioning
confidence: 99%
“…(A) HRV indices obtained in the acute phase. In addition to the investigated traditional linear HRV indices in this study, advanced non-linear HRV indices of complex autonomic control that predict sepsis and related outcome in newborns and adults (8,10,11,31,34) might also be useful in poststroke monitoring. (B) HRV indices obtained in the sub-acute phase (similar patients like in a).…”
Section: Discussionmentioning
confidence: 99%
“…This is because of the link between the immune system and the activity of the autonomic nervous system (ANS), which is reflected in heart rate variability (HRV) indices. However, several studies report that HRV indices are of diagnostic and prognostic value in critical care patients (4,(6)(7)(8)(9) and predict the development of infection and sepsis (10)(11)(12). The regulation of the immune response by the central nervous system and its associations with the cardiac autonomic control assessable with HRV indices are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…For example, using spectral HRV and blood pressure variability analyses in consecutive patients admitted to an ICU, increasing total and LF HRV power were associated with recovery and survival, whereas progressive decreases in HRV were associated with deterioration and death [62]. In separate investigations involving patients in the emergency room [63] or admitted to an ICU after 48 hours [64], decreased total, LF and LF/HF HRV was not only present in patients with sepsis but also correlated with subsequent illness severity, organ dysfunction and mortality. Several reviews discuss the application of HRV spectral analysis to the critically ill patient [65-68].…”
Section: Frequency Domain Analysismentioning
confidence: 99%